Coping COVID- 19 Pandemic Induced Adversities through Parental Involvement: Experiences of Late Adolescents Pursuing Diploma Program from Kathmandu Valley - Subedi, Ramila (Journal of Technical and Vocational Education and Training, 2022)
Amid the truism that pandemics can cause devastating effects on individuals from different group and class, the outbreak of COVID-19 pandemic has exacerbated the situation. In the world that has been experiencing distancing and isolation, adolescents are no exception to the vulnerabilities. However, the risks and adversities they face even seem to have got overshadowed by their engagement with virtual platforms. At the same time, the expectations they have from their parents and the role parental involvement plays for helping them cope with the challenges have remained less discussed. The study, hence, aimed at unraveling how the adolescents experienced COVID- 19 induced adversities and how they coped with them through parental involvement. In this course, three adolescents who have been pursuing diploma Program from the Kathmandu Valley were selected purposively while narrative inquiry was adopted as the method of study. Out of the engagement with the adolescents’ narratives, it was discovered that adolescents experienced socio- economic adversities along with the risk induced by their indulgence in online platforms. At the same time, the adversities were related to the denial they had faced in relation to indigenous skills. Despite this, they were found to have built resilience, and bounced back to normalcy from the adversities with support and engagement of their parents. Hence, the study implies adolescents’ experiences of risks and adversities along with the role of familial and parental involvement in managing the adversities.